Beseprah as Local Wisdom for Developing Culturally Responsive Family Counseling - Dwi Sona; Najlatun Naqiyah; Ari Khusumadewi (Bisma The Journal of Counseling, 2026)
The difficulty in these studies is the lack of culturally reflective family counseling approaches that consider value, communication and family decision making processes within the community. In addition, indigenous knowledge is usually treated as a supplementary story rather than an operational introduction to analyze and elaborate practical family counseling programs. The purpose of this study is to understand the pupose, value construction and practical function of Beseprah as local wisdom and expand its implementation for a cultially relevant family counseling model. Additionally, this research provides theoretical guidelines for family counseling interventions based on Beseprah (C4–6). recruited 24 participants: eight family practitioners, 10 parents, and six youths with Beseprah practice experience. Through semi-structured interview guides, observation sheets and field notes, I gathered the data from the informants in depth interviews, participant observations and document analysis. Findings were interpreted through reflexive thematic analysis, including open coding, categorization and generating themes. Results suggest that Beseprah embodies four moral characteristics: equality, deliberation, respectful hierarchy change, and relationship-based emotion regulation. These are helpful values to use as a base for culturally relevant counseling goals, communication processes, and family conflict resolution. In conclusion, Beseprah has implications for strengthening the competence of multicultural counselors and developing more contextual, local wisdom-based family counseling modules.